Neutrophil and Eosinophil Responses Remain Abnormal for Several Months in Primary Care Patients With COVID-19 Disease - Jukema, B. N.; Smit, K.; Hopman, M. T. E.; Bongers, C. C. W. G.; Pelgrim, T. C.; Rijk, M. H.; Platteel, T. N.; Venekamp, R. P.; Zwart, D. L. M.; Rutten, F. H.; Koenderman, L. (Frontiers in Allergy, 2022)
Introduction: Neutrophil and eosinophil activation and its relation to disease severity has been understudied in primary care patients with COVID-19. In this study, we investigated whether the neutrophil and eosinophil compartment were affected in primary care patients with COVID-19. Methods: COVID-19 patients, aged ≥40 years with cardiovascular comorbidity presenting to the general practitioner with substantial symptoms, partaking in the COVIDSat@Home study between January and April 2021, were included. Blood was drawn during and three to six months after active COVID-19 disease and analyzed by automated flow cytometry, before and after stimulation with a formyl-peptide (fNLF). Mature neutrophil and eosinophil markers at both time points were compared to healthy controls. A questionnaire was conducted on disease symptoms during and three to six months after COVID-19 disease. Results: The blood of 18 COVID-19 patients and 34 healthy controls was analyzed. During active COVID-19 disease, neutrophils showed reduced CD10 (p=0.0360), increased CD11b (p=0.0002) and decreased CD62L expression (p=<0.0001) compared to healthy controls. During active COVID-19 disease, fNLF stimulated neutrophils showed decreased CD10 levels (p=<0.0001). Three to six months after COVID-19 disease, unstimulated neutrophils showed lowered CD62L expression (p=0.0003) and stimulated neutrophils had decreased CD10 expression (p=0.0483) compared to healthy controls. Both (un)stimulated CD10 levels increased 3-6 months after active disease (p=0.0120 and p=<0.0001, respectively) compared to during active disease. Eosinophil blood counts were reduced during active COVID-19 disease and increased three to six months after infection (p<0.0001). During active COVID-19, eosinophils showed increased CD11b (p=0.0139) and decreased (un)stimulated CD62L expression (p=0.0036 and p=0.0156, respectively) compared to healthy controls. Three to six months after COVID-19 disease, (un)stimulated eosinophil CD62L expression was decreased (p=0.0148 and p=0.0063, respectively) and the percentage of CD11bbright cells was increased (p=0.0083 and p=0.0307, respectively) compared to healthy controls. Conclusion: Automated flow cytometry analysis reveals specific mature neutrophil and eosinophil activation patterns in primary care patients with COVID-19 disease, during and three to six months after active disease. This suggests that the neutrophil and eosinophil compartment are long-term affected by COVID-19 in primary care patients. This indicates that these compartments may be involved in the pathogenesis of long COVID.